PENGARUH PENGGUNAAN MEDIA LEAFLET TERHADAP HASIL BELAJAR SEJARAH PADA SISWA KELAS XI IIS MAN 1 PONTIANAK - Saputra, Adi; Sastrawan, Agus; Rahmati, Ika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThis research aims to determine the effect of student learning outcomes using media leaflets on students of class XI IIS Madrasah Aliyah Negeri 1 Pontianak. The method of research used experiemental with One-Group Pre-test post-test design. The sample in this research was the students of Madrasah Aliyah Negeri 1 Pontianak class XI IIS 2. Material taught the period of Japanese government in Indonesia. The research instrument in this research used the form of multiple choice test with 20 questions. The result of student's answer shows the difference of students' learning outcomes. Before the experiment results the average of student learning outcomes was 64.3750 and after the experiments (mean) shows score was 81.5625. The difference in learning outcomes is indicated by the results of a t-test (paired simple T-test) with Ï or significance values of the sig (2-tailed) columns generated through statistical analysis using SPSS version 24 (0,000), smaller than 0,05 = 5% (or 0,000 <0.05), decision-making by comparison of probability values. Based on these results then Ho is rejected, and Ha accepted. Utilization of leaflet media as a medium of learning at this time is not unfamiliar for students of class XI IIS. From the results of these data concluded that leaflet learning media can give effect to the results of student learning class XI IIS 2 Madrasah Aliyah Negeri 1 PontianakÂ Keywords: Effect, Madrasah Aliyah Negeri 1 Pontianak, Media leaflets, Student learning outcomes